Curious George : Halloween double feature : a Halloween boo fest ; spooky fun [videorecording (DVD)]. (Universal Pictures Home Entertainment, 2018)
A Halloween boo fest: Autumn is here, bringing colorful leaves, hay rides, pumpkin patches, and the annual Boo Festival. After hearing about a legendary scarecrow who steals hats, the inquisitive monkey and his friends set out to find him. By the time George gets to the festival, he realizes that it's not always easy to pick the perfect pumpkin and that winning the prize for best costume may be as difficult as catching the mysterious scarecrow.